Effective blended learning practices [ evidence-based perspectives in ICT-facilitated education - Gerbic, Philippa , 1954-; Stacey, Elizabeth , 1949- (Information Science Reference, 2009)
"This book provides insight into the practice of blended learning in higher education"--Provided by publisher.